Manganese-Induced Parkinsonism due to Ephedrone Abuse - Katrin Sikk; Sulev Haldre; Sten-Magnus Aquilonius; Pille Taba (Parkinson's Disease)
During recent years, a syndrome of hypokinesia, dysarthria, dystonia, and postural impairment, related to intravenous use of a “designer” psychostimulant derived from pseudoephedrine using potassium permanganate as the oxidant, has been observed in drug addicts in several countries in Eastern Europe with some cases also in Western countries. A levodopa unresponsive Parkinsonian syndrome occurs within a few months of abusing the homemade drug mixture containing ephedrone (methcathinone) and manganese. The development of this neurological syndrome has been attributed to toxic effects of manganese, but the role of the psychostimulant ephedrone is unclear. This paper describes the clinical syndrome, results of neuroimaging, and therapeutic attempts.